Interference effect of configuration parameters of vertical sand-obstacles on near-surface sand transport - Luo, Xiangying; Li, Jinrong; Tang, Guodong; Li, Yingkun; Wang, Ru; Han, Zhaoen; Feng, Jiaxin; Ren, Tingjie (Frontiers in Environmental Science, 2023)
This study investigates the impacts of height (H) and porosity (P) on the structural properties of wind-driven sand flux in vertical sunflower straw sand-obstacles. We conducted an experiment on sand transport within barriers of various configurations within a 1 m proximity to the surface. In tandem, we monitored wind velocity and direction within the barriers, analyzed total sand transport rate, sand-blocking effects, and cumulative sediment transport rate heights for various parameter configurations, and devised a best sand transport flux model for use within the sand-obstacle. The efficacy of vertical sunflower stalk sand-obstacles in mitigating sand movement has been demonstrated to fall within the range of 37.26%–92.31%. This study reveals a significant correlation between barrier height and porosity in achieving this effect (p < 0.05). High and densely configured sand-obstacles lead to an accumulation of intercepted sand material in front of the front row of the sand-obstacle. In contrast, low and sparsely arranged sand-obstacles exhibit a delayed state of sand material accumulation. Furthermore, with an increase in the height of the obstacle and a decrease in porosity, there is a diminishing trend in the sand transport rate within the obstacle. Concurrently, the height of sand transport within the barrier exhibits an upward trend. A three-parameter exponential function has been employed to more precisely simulate the wind-sand flow structure characteristics within a 1-m height range of the barrier. These research findings contribute to an enhanced understanding of the impact of different vertical sand-obstacle configurations on near-surface wind-driven sand transport patterns in active desert areas. Moreover, they furnish both theoretical underpinnings and practical guidance for the scientific configuration of vertical sand-obstacles.